Alternative Design Solutions For Flexible And Rigid Pavements In The Sampang-Ketapang Road Widening Project (Section 113) - Muhammad Zainal Muttaqin; Esti Wulandari; Laksono Djoko Nugroho (Syntax Corporation Indonesia, 2025)
The Sampang-Ketapang road segment (Link 113) plays a pivotal role in regional connectivity, supporting economic and social activities in Sampang Regency, a hub for salt and tobacco production. This study compares two pavement design alternatives: flexible pavement using Class A aggregate with a thickness of 200 mm and rigid pavement with a flexural strength of 4.5 MPa and a thickness of 300 mm. The analysis evaluates cost efficiency, implementation time, and suitability for the increasing traffic demands of the region. The results show that flexible pavement requires an investment of IDR 12.8 billion and a 7-month construction duration, while rigid pavement demands IDR 19.5 billion and a 9-month duration. Flexible pavement offers lower initial costs and shorter implementation time, making it a more feasible option for segments with moderate traffic. However, it requires more frequent maintenance, increasing long-term expenses. Conversely, rigid pavement is more durable, with minimal maintenance costs, but has higher initial costs and a longer construction timeline. Considering the economic and technical aspects, flexible pavement is recommended as the optimal solution for this project due to its cost-effectiveness and shorter timeline, ensuring efficient resource utilization. Strategic implementation combining both pavement types is also proposed, with flexible pavement for moderate traffic areas and rigid pavement for segments with heavy traffic. This approach balances cost efficiency, implementation time, and long-term durability, supporting the sustainable development of road infrastructure in Sampang Regency